2005
DOI: 10.1149/1.1873452
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Gallium-Containing Carbon Deposit Produced by Decomposition of Trimethyl Gallium

Abstract: The composition, morphology, and structure of a gallium-containing carbon deposit that forms under certain conditions during hydride-organometallic vapor phase epitaxy ͑HOMVPE͒ of GaN were characterized by several techniques. The deposits are produced during pyrolysis of trimethyl gallium and results in gas-phase depletion of Ga, which reduces the growth rate and reproducibility of GaN growth. The morphology of the deposit depended on temperature, changing from granular to tubular-shape, and then to powder-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The heterogeneous thermolysis of GaMe 3 was reported to form a metallic gallium core with a carbon shell [28]. This agrees with the TPD study performed by Flores et al [11], which shows the desorption of hydrogen, but no carbon-containing species at high temperature.…”
Section: Trimethylgalliumsupporting
confidence: 89%
“…The heterogeneous thermolysis of GaMe 3 was reported to form a metallic gallium core with a carbon shell [28]. This agrees with the TPD study performed by Flores et al [11], which shows the desorption of hydrogen, but no carbon-containing species at high temperature.…”
Section: Trimethylgalliumsupporting
confidence: 89%
“…CMTs are synthesized as arrays directly on silicon (Si) substrates. The CMT synthesis procedure and the structure have been described in detail elsewhere. Although the present technique of using trimethyl gallium is expensive, this process presents a route of using Ga as a catalyst in the presence of methyl radical species for the inexpensive large-area synthesis of CMTs. The SEM image in Figure a shows a large area of the as-synthesized CMTs that are several micrometers in length.…”
Section: Resultsmentioning
confidence: 99%
“…28,29 Another study showed that these CMTs can be synthesized during thermal decomposition of a Ga precursor. 30 Recently, Sn particles encapsulated in porous multichannel carbon microtubes have shown a capacity retention of ∼650 mAh g -1 after 140 cycles. 31 In our present study, for the first time, we report the * To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One known way to overcome this problem is to use an organometallic [37][38][39] or organometallic chloride [40][41][42] precursor that is converted to gallium monochloride in the hot zone of the reactor by reaction with hydrogen chloride or by decomposition, respectively. The drawback of this approach is the possible carbon contamination and the formation of condensed carbon co-products [43].…”
Section: B External Boatmentioning
confidence: 99%